Linguistic and Cultural Acquisition in a Migrant Community; Editors: David Singleton, Vera Regan and Ewelina Debaene; Publisher: Multilingual Matters; 2013; ISBN: 9781847699893; Pages: 200 - Waniek-Klimczak, Ewa (Studies in Second Language Learning and Teaching, 2013)
Book review